2005
DOI: 10.1111/j.1464-410x.2005.05854.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in bladder nerve‐growth factor and p75NTR genetic expression in streptozotocin‐induced diabetic rats

Abstract: immunosorbent assay. Expressions of the mRNAs that encoded NGF and NGF receptor p75 NTR in the rat bladder were evaluated using reverse transcription-polymerase chain reaction. RESULTSThe mean ( SEM ) NGF level in the STZ-diabetic rat bladder was significantly lower than in the control group, at 56.56 (8.28) and 84.33 (11.05) pg/ µ g protein, respectively ( P < 0.01). The mRNA expressions of bladder NGF and p75 NTR in the diabetic rats were significantly lower than in the control group ( P < 0.05 and < 0.001, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
24
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 33 publications
8
24
0
Order By: Relevance
“…Previous studies have shown that deficient retrograde axonal transport of NGF from target organs to sensory pathways may play an important role in diabetic neuropathy onset, and proNGF is capable of inducing apoptosis [13,15]. Our experimental results agree with previous studies [20,21]; we found that 8-week DM rats showed a remarkable decrease in NGF mRNA and protein levels in urethra compared to control rats. Based on these results, several studies have treated diabetic neuropathy with NGF supplement therapy, which significantly improved voiding function without affecting bladder nociceptive responses [22].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Previous studies have shown that deficient retrograde axonal transport of NGF from target organs to sensory pathways may play an important role in diabetic neuropathy onset, and proNGF is capable of inducing apoptosis [13,15]. Our experimental results agree with previous studies [20,21]; we found that 8-week DM rats showed a remarkable decrease in NGF mRNA and protein levels in urethra compared to control rats. Based on these results, several studies have treated diabetic neuropathy with NGF supplement therapy, which significantly improved voiding function without affecting bladder nociceptive responses [22].…”
Section: Discussionsupporting
confidence: 83%
“…In vivo studies have shown reductions in the number of dorsal root ganglion neurons in both p75exonIII-/- and the p75exonIV-/- gene-targeted mice, and these findings provide additional support that p75 NTR can promote neuronal survival [28]. The results of our study agree with the hypothesis of Tong and Cheng [21], who posited that decreased NGF and p75 NTR expression levels might be responsible for diabetic peripheral neuropathy.…”
Section: Discussionsupporting
confidence: 82%
“…In patients with neuropathic bladder, increased expression of p75 NTR has been shown in the umbrella and basal layers of the urothelium, in addition to being expressed in bladder nerves (Vaidyanathan et al, 1998). In contrast, p75 NTR mRNA is decreased in urinary bladder or sensory neurons in the DRG (Delcroix et al, 1998) of streptozotocin-induced diabetic rats but restoration of normal blood glucose level or exogenous, systemic treatment with NGF returned transcript expression to normal in urinary bladder (Tong and Cheng, 2005) or DRG (Delcroix et al, 1998). Thus, a number of studies have demonstrated that p75 NTR expression is modifiable in the urinary bladder.…”
Section: Discussionmentioning
confidence: 77%
“…Although numerous studies have suggested a central or peripheral role for p75 NTR after axotomy (Wakabayashi et al, 1998;Keast and Kepper, 2001;Hannila and Kawaja, 2005;Scott et al, 2005;Obata et al, 2006) or peripheral somatic inflammation (Cho et al, 1996;Pezet et al, 2001;Chien et al, 2007), few studies have examined the role of p75 NTR in normal or inflamed lower urinary tract pathways (Wakabayashi et al, 1996(Wakabayashi et al, , 1998(Wakabayashi et al, , 2002Vaidy- anathan Elsasser-Beile et al, 2000;Jahed and Kawaja, 2005;Tong and Cheng, 2005). To our knowledge, no studies have examined changes in p75 NTR expression in central or peripheral micturition reflex pathways after bladder inflammation.…”
Section: Discussionmentioning
confidence: 93%
“…Sasaki et al [29] showed a long-term gradual decrease in NGF levels in the bladder and L6-S1 dorsal root ganglia of diabetic rats. Tong and Cheng [30] also showed a decrease in genetic expression of NGF in chemically induced diabetic rats. Targeted gene therapy against the dorsal root ganglia can increase the expression of NGF, resulting in increased bladder activity in diabetic rats [28].…”
Section: Pathophysiologymentioning
confidence: 92%